Contextualising health screening risk assessments in police custody suites - qualitative evaluation from the HELP-PC study in London, UK - Iain McKinnon; Tracy Finch (BMC, 2018)
Abstract Background In the UK, police custody officers have a responsibility to screen for health morbidity and vulnerability among detainees. This study aimed to develop an understanding of the barriers to performing effective health screening in police custody suites, understand the impact of screening tools on practice within the custody suite, and to identify factors that could hinder or facilitate the future implementation of a new screening intervention in this environment. Methods A qualitative study was conducted alongside a quantitative evaluation of a novel screening tool. Qualitative methods included observation of the custody environment, semi-structured interviews with police staff, and elicitation of comments from detainees about their experiences of screening. Data were analysed inductively using thematic analysis. Normalization Process Theory (NPT) was used to inform data collection and as a framework for higher level analysis of findings. Results Five overall constructs were identified that develop understanding of the integration of health screening within custody: the workability of risk assessment screening tools; the effect of the custody environment and the people therein; shifts in professional roles and interrelationships amongst staff; cultural responses to risk and liability in police work; how infrastructure, knowledge and skills can impact on detainee safety. Conclusions Health and risk assessment screening in police custody is a complex and demanding activity which extends beyond the delivery of a screening tool. Professional roles, the demanding environment and police culture impact on the overall process. Recommendations for improved integration of health and risk assessment screening in wider police custody practice are proposed.